Clinical research on traditional Chinese medicine for Postherpetic neuralgia: an evidence map - Luo, Yongyuan; Yang, Tingyu; Hong, Zhongxi; Huang, Chen; Xiong, Xiya; Zhou, Xianyu; An, Xuemei (Frontiers in Neurology, 2025)
ObjectiveThis evidence mapping review evaluated clinical research on traditional Chinese medicine (TCM) for postherpetic neuralgia (PHN) to identify evidence distribution and gaps, thereby informing future studies.MethodsA systematic search was conducted in PubMed, Embase, Web of Science, the Cochrane Library, CBM, CNKI, and Wanfang databases for randomized controlled trials (RCTs) and systematic reviews (SRs)/meta-analysis (MAs) published up to December 2024. Data were extracted on publication trends, sample sizes, TCM pattern types, intervention types and duration, outcome indicators, and methodological quality. The evidences were analyzed and presented through a combination of text and graphical formats.ResultsA total of 976 RCTs and 24 SRs/MAs were included. RCTs showed fluctuating growth, yet typically had small samples (51–100 cases). Qi stagnation and blood stasis was the most common TCM pattern. The main intervention was multi-therapy combination, with treatment duration primarily between 4 and 8 weeks. Outcome indicators mainly focused on total effective rate, pain intensity, and safety evaluation, while neglecting pain area, self-care ability, and neurotrophic factors. Furthermore, methodological quality assessment revealed suboptimal design rigor across both RCTs and SRs/MAs.ConclusionTCM shows potential benefits for PHN but faces challenges in study design and outcome standardization. Future research should prioritize multicenter, large-scale RCTs with rigorous methodologies and harmonized outcome assessments. Meanwhile, enhancing the quality of SRs/MAs and integrating evidence-based frameworks will help bridge clinical practice with evidence-based TCM for PHN.